Photography and the Organic Nonhuman: Photographic Art with Light, Chlorophyll, Yeasts, and Bacteria - Vuorinen Jane (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
The concept of nonhuman in relation to photography has recently been mostly theorized through technology, while organic nonhuman agents and processes at work in photography have received less attention. In this article, works by three contemporary Finnish artists who incorporate organic materials and processes into photography are analyzed to renegotiate the borders between photography, bioart, and science. This leads to a rethinking of the dichotomy between the concepts of technological and organic in the context of contemporary photographic art. Combining new materialist and posthumanist theories with photography history and theory allows for a multidisciplinary method that recognizes the worth of both human and nonhuman agents and processes at work. The artworks are analyzed as temporal and processual, taking into account their performative qualities.